Low-dimensional Magnetism in Compounds with Different Dimensions of Magnetic Interaction - M. S. Baranava (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2022)
The results of a comparison of the exchange interaction mechanisms in low dimensional magnetic systems are presented. It has been shown that ZnO crystal may be used as a semiconductor non-magnetic matrix for the formation of quasi-one-dimensional and quasi-zero-dimensional magnetic systems by introducing impurity atoms of Cr, Mn, Fe, Co and Ni. Structural parameters, electronic and magnetic properties were calculated at the atomic level in the framework of quantum mechanical simulation. The exchange interaction integrals were calculated at the microscopic level using the Heisenberg model. The exchange interaction mechanisms were determined on the obtained dependences of the exchange interaction integral on the structural and electronic properties, as well as on the features of the low-dimensional magnetic systems partial density of electronic states. The results of studying the exchange interaction mechanisms in two-dimensional magnetic systems formed in materials of the MAX3 (M= Cr, Fe, A = Ge, Si, X= S, Se, Te) group are summarized. The established mechanisms made it possible to compare the conditions for the formation of a ferromagnetic order in systems with different dimensions of magnetic interaction. The ferromagnetic order in all the structures under study is formed due to the indirect superexchange interaction between orbitals of different symmetry. Strategies aimed at enhancing the superexchange interactions between orbitals of different symmetry or attenuating the contributions of the exchange interaction between orbitals of the same symmetry contribute to the formation of stable hightemperature ferromagnetism.